2007
DOI: 10.1590/s1415-47572007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent in situ hybridization (FISH) as a diagnostic tool for Williams-Beuren syndrome

Abstract: Fluorescent in situ hybridization (FISH) with commercial probes covering the elastin gene (ELN) was used to determine the frequency of the 7q11.23 deletion in 18 children clinically diagnosed with Williams-Beuren syndrome (WBS). A de novo deletion was detected in 15 of the children (83%). Diagnostic investigation for WBS started late in childhood (median = 5.8 years). All the children showed facial features typical of the syndrome, mental retardation and developmental delay. Over-friendliness was observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…Nineteen participants with WS were recruited from the Williams Syndrome Foundation UK. Diagnosis of WS in all participants had previously been confirmed by a clinician and a positive Fluorescence In Situ Hybridization (FISH) test to ensure deletion of the elastin gene, observed in 95% of those with WS (de Souza, Moretti‐Ferreira, & Rugolo, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Nineteen participants with WS were recruited from the Williams Syndrome Foundation UK. Diagnosis of WS in all participants had previously been confirmed by a clinician and a positive Fluorescence In Situ Hybridization (FISH) test to ensure deletion of the elastin gene, observed in 95% of those with WS (de Souza, Moretti‐Ferreira, & Rugolo, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…However, former standard methodologies, such as FISH, are still considered the gold standard for the detection of rare conditions, mainly in developing countries where financial support is limited and affordable technologies are preferred. 2 , 6 , 7 , 53 55 …”
Section: Discussionmentioning
confidence: 99%
“…FISH probes covering the ELN gene detect the majority of the deletion in children clinically diagnosed with WBS. 39 , 53 , 54 Nickerson et al 39 showed that more than 90% of the patients were hemizygous for the elastin gene, while Souza et al 53 verified that 83% of the children clinically diagnosed with WBS had the same deletion. Moreover, Ramírez-Velazco et al 54 analyzed patients clinically diagnosed with WBS and identified that 66% of them had the 7q11.23 deletion detected by FISH.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of WS in all participants had previously been confirmed by a clinician and a positive fluorescence in situ hybridization test to ensure deletion of the elastin gene, observed in 95% of those with WS (D'Souza, Moretti-Ferreira, & Rugolo, 2007). Three participants had to be excluded from the analyses because they showed a strong response bias (100% rejection or 100% acceptance of test sequences) during the AGL task, or did not complete the task.…”
Section: Participantsmentioning
confidence: 99%